Fault simulation and fuzzy controller for high pressure heater in thermal power plant (writers from India) - Srinivasan, S.; Kanagasabapathy, P.; Chitra, K.; Pugazhendi, R.; Selvaganesan, N. (Faculty of Electrical Engineering, 2006)

(untitled)
This paper presents fault simulation and design of fuzzy logic controller for a high pressure heater in a thermal power plant. An analytical model for the system has been presented in the nonlinear state space form based on fundamental physical laws. The mathematical model is validated with the real time plant data. A fuzzy controller is developed, which performs like a classical proportional plus integral controller, giving the level reference variation based on error in condensate level inside a heater and its change. The state variables are estimated for the normal and faulty condition using the model which is simulated using the plant data. The performances of both controllers are evaluated and the faults are simulated using Matlab simulink.